DINAMIKA EARNINGS MANAGEMENT: IMPLIKASI DARI KUALITAS AUDIT, KOMITE AUDIT, DEWAN KOMISARIS, DAN KEPEMILIKAN INSTITUSIONAL - Khairunisa Santoso; Barlia Annis Syahzuni (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This research aims to empirically examine the effect of audit quality, audit committee, board of commissioners, and institutional ownership on earnings management practices.. The research employs a quantitative method with a causality design, involving independent variables such as audit quality (Big Four or Non Big Four), audit committee (annual meeting frequency), board of commissioners (annual number of meetings), and institutional ownership (percentage of share ownership by institutions), with earnings management as the dependent variable. Earnings management is measured using Discretionary Accruals from the Modified Jones Model (1995). The study population includes 84 companies in the food and beverage subsector for the period 2019-2022, with a sample of 27 companies or 108 data points meeting the criteria. Statistical software analysis shows that earnings management is significantly influenced by audit quality, audit committee, board of commissioners, and institutional ownership in a simultaneous manner. Partially, only audit quality and board of commissioners significantly and negatively influence earnings management, while audit committee and institutional ownership do not have a significant impact. This research provides implications for companies to increase managerial supervision and transparency in financial reporting, as well as strengthen the role of the audit committee and board of commissioners to prevent earnings management.